The effects of Pediococcus acidilactici MA18/5M on growth performance, gut integrity, and immune response using in vitro and in vivo Pacific salmonid models - Soto-Dávila, Manuel; Langlois Fiorotto, Luana; Heath, John W.; Lumsden, John S.; Reid, Gregor; Dixon, Brian (Frontiers in Immunology, 2024)
Microbial management is central to aquaculture’s efficiency. Pediococcus acidilactici MA18/5M has shown promising results promoting growth, modulation of the immune response, and disease resistance in many fishes. However, the mechanisms through which this strain confers health benefits in fish are poorly understood, particularly in Pacific salmonid models. Briefly, the aims of this study were to i) assess the protective effects of P. acidilactici MA18/5M by examining gut barrier function and the expression of tight junction (TJ) and immune genes in vitro and in vivo, and ii) to determine the protective effects of this strain against a common saltwater pathogen, Vibrio anguillarum J382. An in vitro model of the salmonid gut was employed utilizing the cell line RTgutGC. Barrier formation and integrity assessed by TEER measurements in RTgutGC, showed a significant decrease in resistance in cells exposed only to V. anguillarum J382 for 24 h, but pre-treatment with P. acidilactici MA18/5M for 48 h mitigated these effects. While P. acidilactici MA18/5M did not significantly upregulate tight junction and immune molecules, pre-treatment with this strain protected against pathogen-induced insults to the gut barrier. In particular, the expression of ocln was significantly induced by V. anguillarum J382, suggesting that this molecule might play a role in the host response against this pathogen. To corroborate these observations in live fish, the effects of P. acidilactici MA18/5M was evaluated in Chinook salmon reared in real aquaculture conditions. Supplementation with P. acidilactici MA18/5M had no effect on Chinook salmon growth parameters after 10 weeks. Interestingly, histopathological results did not show alterations associated with P. acidilactici MA18/5M supplementation, indicating that this strain is safe to be used in the industry. Finally, the expression pattern of transcripts encoding TJ and immune genes in all the treatments suggest that variation in expression is more likely to be due to developmental processes rather than P. acidilactici MA18/5M supplementation. Overall, our results showed that P. acidilactici MA18/5M is a safe strain for use in fish production, however, to assess the effects on growth and immune response previously observed in other salmonid species, an assessment in adult fish is needed.